If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 4)(x + -3) = 5x Reorder the terms: (4 + x)(x + -3) = 5x Reorder the terms: (4 + x)(-3 + x) = 5x Multiply (4 + x) * (-3 + x) (4(-3 + x) + x(-3 + x)) = 5x ((-3 * 4 + x * 4) + x(-3 + x)) = 5x ((-12 + 4x) + x(-3 + x)) = 5x (-12 + 4x + (-3 * x + x * x)) = 5x (-12 + 4x + (-3x + x2)) = 5x Combine like terms: 4x + -3x = 1x (-12 + 1x + x2) = 5x Solving -12 + 1x + x2 = 5x Solving for variable 'x'. Reorder the terms: -12 + 1x + -5x + x2 = 5x + -5x Combine like terms: 1x + -5x = -4x -12 + -4x + x2 = 5x + -5x Combine like terms: 5x + -5x = 0 -12 + -4x + x2 = 0 Factor a trinomial. (-2 + -1x)(6 + -1x) = 0Subproblem 1
Set the factor '(-2 + -1x)' equal to zero and attempt to solve: Simplifying -2 + -1x = 0 Solving -2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2Subproblem 2
Set the factor '(6 + -1x)' equal to zero and attempt to solve: Simplifying 6 + -1x = 0 Solving 6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 0 + -6 -1x = 0 + -6 Combine like terms: 0 + -6 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6Solution
x = {-2, 6}
| -24x-3(-8x+2)=1 | | -x-4(2)=-5 | | 8(2x-1)-5(2x+3)=-5 | | -8-28=13-9x | | -2x+2(-3x-13)=10 | | (2x-5)2=121 | | 2x+9y=10 | | 8x+32=3x+3 | | 7(1-x)-6(2-x)=8 | | x^3-14x^2+39x+54=0 | | 3a-12a-15=0 | | 5(x+1)+5(x-1)=30 | | x+0.10x+0.05x=40 | | 10m+32m=-5 | | m-3m=-10 | | 3(x-11)(x+10)=0 | | 7(x+10)-3=73 | | x^2+15x+30=6 | | m-1/3=5/12 | | 5x+5-9x=-11 | | 2x+7+4(2X+3)=-1 | | Logy=25 | | 3/2x-14=16 | | 8-2x=1+x | | x=1.42x-60 | | 7+6p=3+2(1-p) | | x=1.42x-8 | | 17x+13y=1 | | 4x+7=7x+13 | | 4-(x+y^2)=0 | | 3x^2-3x-90= | | 2/3x-8+5/3x |